Facial nerve palsy, headache, peripheral neuropathy and Kaposi’s sarcoma in an elderly man - Daoussis, Dimitrios; Chroni, Elisabeth; Tsamandas, Athanassios C; Andonopoulos, Andrew P (World journal of clinical cases, 2014)
We present a case of an elderly man, who initially presented with right facial nerve palsy, ipsilateral headache, elevated erythrocyte sedimentation rate (ESR) and no fever. A presumptive diagnosis of giant cell arteritis was made and the patient was treated with high-dose steroids. A temporal artery biopsy was negative. Several months later, while on 16 mg of methylprednisolone daily, he presented with severe sensorimotor peripheral symmetric neuropathy, muscle wasting and inability to walk, uncontrolled blood sugar and psychosis. A work-up for malignancy was initiated with the suspicion of a paraneoplastic process. At the same time a biopsy of the macular skin lesions that had appeared on the skin of the left elbow and right knee almost simultaneously was inconclusive, whereas a repeat biopsy from the same area of the lesions that had become nodular, a month later, was indicative of Kaposi's sarcoma. Finally, a third biopsy of a similar lesion, after spreading of the skin process, confirmed the diagnosis of Kaposi's sarcoma. He was treated with interferon α and later was seen in very satisfactory condition, with no clinical evidence of neuropathy, normal muscle strength, no headache, normal electrophysiologic nerve studies, involution of Kaposi's lesions and a normal ESR.